Research on China's Digital Divide and its Bridging - Sang, Yuxuan (International Journal of Social Sciences and Public Administration, 2024)
To address the adverse impacts of the digital divide on social inequality and economic development, this study delves deeply into the causes and effects of the digital divide, particularly as manifested between the eastern and western regions of China, aiming to propose effective mitigation strategies. Employing a longitudinal data analysis approach, combined with four decades of tracking data, the study quantitatively compares the disparities in digital technology penetration, educational attainment, and economic growth between the east and west. Qualitative analysis complements this, providing insights into the dynamic changes and underlying mechanisms of the digital divide. The findings reveal that the digital divide is significantly present across regions, closely linked to educational disparities and constraints on economic growth potential. Innovative strategies, such as tailored digital education initiatives and infrastructure investment, have proven effective in promoting technological diffusion and narrowing the gap, offering more targeted and practical solutions compared to conventional one-size-fits-all approaches. This research not only deepens our understanding of the complexities of the digital divide but also provides a strategic framework that offers substantial theoretical support and practical guidance for policymakers. It holds significant theoretical and practical implications for advancing balanced regional development, fostering social equity, and facilitating digital transformation.